Global prospects for cultivating Centella asiatica: An ecological niche modeling approach under current and future climatic scenarios - Pei-Chen Lin; Tzen-Yuh Chiang; Miaw-Ling Chen; Tsai-Wen Hsu; Po-Wu Gean; Sheng-Tzong Cheng; Yu-Hsun Hsu (Journal of Agriculture and Food Research)
Centella asiatica is a medicinal plant recognized for its various benefits contributed by its metabolites and has been used as a food supplement since prehistorical times across various cultures. Due to the reliance on natural populations of C. asiatica and the impacts of environmental factors on its yield and centelloside production, there is a need to identify suitable cultivation areas for this species. We employed ecological niche modelling with bioclimatic and soil variables to evaluate the suitability of cultivation under current and future climatic scenarios. Our results identified suitable areas for cultivating C. asiatica worldwide, indicating its potential for global commercial cultivation. However, the niche reconstruction of highly concentrated centelloside was restricted to South and Southeast Asia due to the lack of available data. When we projected the modelled niche of centelloside in these regions, we observed a lower occurrence probability in some areas, suggesting potential challenges in cost-effectiveness. Nevertheless, our results suggest a consistent future distribution for this species when we projected the modelled niche under future climates based on various socio-economic scenarios. This study not only identifies suitable areas to develop commercial cultivation for C. asiatica with highly concentrated centelloside, but also provides supporting evidence of the consistency of these areas, which can increase its sustainability.